Modern treatment options for systemic lupus erythematosus in children (literature review) - M. I. Kaleda; I. P. Nikishina (Современная ревматология)
The treatment of juvenile-onset systemic lupus erythematosus (jSLE) is a complex task in view of the diversity of clinical manifestations and the course of the disease as well as the high risk of organ damage. The need to create separate therapeutic principles for jSLE is justified by the greater intensification of therapy due to both the doses used and the combination of a larger number of different drugs in a patient. However, the basis for the treatment of jSLE today is mainly the extrapolation of data obtained in studies with adult patients. The review reflects modern ideas about the spectrum of drugs used in jSLE, with particular emphasis on efficacy, safety and timing of therapy as well as possible optimization options.